The Use of Antiviral Drugs for Influenza: Guidance for Practitioners 2012/2013 - Fred Y Aoki; Upton D Allen; H Grant Stiver; Gerald A Evans (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present article addresses the use of antiviral drugs in the management of seasonal influenza illness for the 2012/2013 season. It updates the previous document published in 2011 (1). Noteworthy guidance updates since 2011 include the following: Seasonal influenza in 2012/2013 is predicted to be caused by two human influenza A and one influenza B strain, all of which are anticipated to remain generally susceptible to oseltamivir.The predicted strains are A/California/7/2009 (H1N1) pdm09-like, A/Victoria/361/2011 (H3N2)-like and B/Wisconsin/1/2010-like (Yamagata lineage). All are included in the seasonal influenza vaccine and are susceptible to oseltamivir.Swine-variant H3N2v, which has rarely caused infection in humans exposed to infected swine within the past year in the United States, is susceptible to oseltamivir. It is not included in the current seasonal influenza vaccine.It is still considered that initiation of antiviral therapy more than 36 h to 48 h after onset of symptoms is beneficial in patients hospitalized with complicated influenza and severe illness.Oseltamivir continues to be recommended for the treatment of influenza in pregnant women.The use of antiviral drugs among measures to control outbreaks of influenza in closed facilities such as correctional institutions is now included in the present document.